Universitas Sumatera Utara Arboretum of Deli Serdang, North Sumatra, Indonesia: Revealing the potency - Nuryawan Arif; Rahmawaty; Susilowati Arida; Zaitunah Anita; Anjelisa Zaitun Hasibuan Poppy; Irawan Bambang; Fadillah Achmad (BIO Web of Conferences)
Growth, development, and structural changes within the Universitas Sumatera Utara Arboretum since its establishment in 2005 should be recognized, observed, and investigated. Previously, the site of this arboretum was oil palm plantation. The objective of this study is to map, classify, identify, and calculate the potency of the vegetation within the arboretum. Method of this research is combination of literature study and field work. In this research, literature study, site visit, and inventory work were reported. Results of literature study revealed that at least 56 species of forestry plants were found in 2008 and increased up to 77 species of tree were found in 2023. Present research conducted in 2024 using a systematic sampling with random start with 36 plots revealed only 53 species of tree. The result was lower due to differ in method. To promote climate change mitigation, it is still necessary to optimize the potency as a source of bio-energy, food and feed, herbal medicine, carbon reserves, and creative economy (natural dyes and craft materials).